2022
DOI: 10.1111/sjop.12861
|View full text |Cite
|
Sign up to set email alerts
|

Clinician experiences of homework in couples and family therapy: A survey of perceived impact on the working alliance

Abstract: The process of engaging clients in homework assignments has been studied extensively in research settings, but rarely have the challenges in the implementation of the science been considered in couples and family therapy. A survey was conducted of 226 clinicians regarding (1) their experience of homework adherence (quantity and quality) with couple and family clients, and (2) their experience of the impact of homework non‐completion (IHN) on the working alliance. Clinicians working with families reported less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Therapist behavior has primarily been studied in relation to BSH adherence or compliance, and it is important to consider that therapist behaviors regarding BSH may have other unmeasured impacts (Kazantzis et al, 2022). Crucially, if the therapist has less than optimally selected and planned the task with the client, there is potential for negative views of the task, or negative interpretations of the process for the BSH, all of which will then impact on the completion (see theoretical model in Kazantzis & Miller, 2022).…”
Section: Assessmentmentioning
confidence: 99%
“…Therapist behavior has primarily been studied in relation to BSH adherence or compliance, and it is important to consider that therapist behaviors regarding BSH may have other unmeasured impacts (Kazantzis et al, 2022). Crucially, if the therapist has less than optimally selected and planned the task with the client, there is potential for negative views of the task, or negative interpretations of the process for the BSH, all of which will then impact on the completion (see theoretical model in Kazantzis & Miller, 2022).…”
Section: Assessmentmentioning
confidence: 99%
“…Psychotherapy is not universally beneficial. BSH, too, may prove either productive and conducive to the therapeutic process, or stressful and potentially counterproductive (Kazantzis et al, 2023). For instance, BSH may activate negative beliefs and instill feelings of pressure, anxiety, and fear of failure in some clients (Barnes et al, 2013; Fehm & Mrose, 2008; Finning et al, 2017), and has even been reported as the most significant challenge in treatment (Barnes et al, 2013).…”
Section: Potential Adverse Effects and Possible Barriers To Bsh Engag...mentioning
confidence: 99%